Introducing the Academic Discipline of Agricultural Communications to the United Kingdom - Jefferson D. Miller; Sara Maples Bell; Jill Rucker; Emily Buck; Anika Parks (Journal of Applied Communications, 2020)
Though the academic discipline of agricultural communications is well established in the United States, it does not have a significant presence in the United Kingdom. This is the case in spite of the fact that the profession of agricultural communications is well-established across the country. As administrators at U.K. institutions consider adding curriculum in this discipline, it is important for them to have an understanding of the competencies employers would expect of agricultural communications graduates, as well as an understanding of what students would expect to learn. Empirical data describing such perceptions could further the conceptualization and development of the discipline in the U.K. A total of 22 agricultural communications professionals and 67 agricultural students from land-based institutions in England and Scotland completed the survey. Data demonstrated that agricultural students’ and agricultural communications professionals’ perceptions were generally not statistically different. While many of the competencies that guide agricultural communications curriculum in the U.S. were perceived as important to U.K. professionals and students alike, both groups perceived competencies such as writing skills and general communication skills to be especially important for prospective agricultural communications graduates in the U.K. Future studies should continue to investigate the need for an agricultural communications academic discipline in the communications profession in the United Kingdom and preferences of students, faculty, and potential employers of agricultural communications graduates.
Keywords: Academic programs; curriculum development; teaching